From burnout to growth: the relationship between teachers’ job satisfaction, wellbeing and mental health - Cefai, Carmel; Galea, Natalie; Spiteri, Rachel; Cavioni, Valeria (Frontiers in Education, 2025)
In contrast to previous studies focused on the negative impact of teacher stress and burnout, recently there has been a shift towards processes which help to support teachers’ wellbeing and mental health. The objective of the present study is to examine the status of the job satisfaction, wellbeing, and mental health of schoolteachers in Maltese schools and examine the interrelations between these key variables. A total of 351 primary and secondary school teachers completed an anonymous online survey on their mental health, wellbeing, and job satisfaction. The findings portray a mixed profile of teachers experiencing a moderate level of distress, but feeling connected and efficacious, and having mixed feelings about different aspects of their profession. Job satisfaction, particularly relationships with colleagues and nature of work, and sense of wellbeing, particularly connectedness, foster teachers’ mental health and help to protect them against burnout and mental health issues. School connectedness appears to be one of the strongest health promoting and protective factors. On the other hand, young teachers with limited experience are the least satisfied and have lower levels of mental health and wellbeing, making them more at risk of burnout and attrition. Various recommendations are made on how to enhance the wellbeing and mental health of practicing teachers and make the profession more rewarding for early career teachers.